Forests in sustainable mountain development : a state of knowledge report for 2000 (IUFRO research series ;, 2000)
Written by leading international authors, this book presents a comprehensive review of forests in mountain regions, and of their importance for sustainable development. The book has been prepared under the auspices of the IUFRO Task Force on Forests in Sustainable Mountain Development, for the IUFRO Congress held in August 2000. It addresses current issues and initiatives, in particular what is known about an issue or area, its importance, and priorities for future research and action. Key global topics are addressed in general articles, and many specific regional and local issues are described in shorter case studies. The book is relevant to those studying and researching in forestry, geography, development, and environmental and mountain studies. After a foreword (Linking mountain forests conservation with sustainable human development, Mishra, H. R.) the book is arranged in 10 main sections, each with separate papers, some with case studies following them: (1) Mountain forests: location, characteristics and trends, 7 papers, 1 large foldout map of the mountains, and the mountain forests of the world; (2) Mountain communities and their forests, 5 papers; (3) Interdependencies between mountain and lowland populations, 3 papers; (4) Perceiving and assuring the multiple functions of mountain forests, 5 papers; (5) Multiple functions from mountain forests I. Mountain forests: sources of wood, 4 papers; (6) Multiple functions from mountain forests II. Agroforestry and non-timber forest products, 4 papers; (7) Multiple functions from mountain forests III. Diverse societal benefits, 9 papers; (8) Legislation, policies and economic instruments, 4 papers; (9) Institutions for mountain forests, 5 papers; and (10) Research, implementation and communication, 4 papers. The references are all at the end of the book, and a subject index is included. All the papers are noticed separately (with the associated case studies listed) on the CAB ABSTRACTS database.